Electronic Fans: A pathogen reservoir and potential cross-contamination source - Vance Bergeron; Amine Metahni; Francis Derouin (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2020)
With the recent outbreak of COVID-19 the concern for airborne pathogens has increased. It is clear now that taking preventative measures such as wearing masks and social distancing are important to abate the spread and transmission of airborne pathogens. It is also equally important to identify and minimize the different sources of both direct and cross-contamination. Here we identify one source that has thus far not been considered: electronic fans used to cool the electronic components in equipment used throughout our daily lives; computers, hospital instruments, and significantly airborne samplers. Airborne samplers used to evaluate airborne pathogens must have their fan air exiting the device filtered, otherwise the device itself can be an important source as different location are sampled, moving the pathogen load from one location to another.